Kajian Sistem Pengkondisian Udara untuk Meningkatkan Tingkat Kenyamanan Termal pada suatu Ruangan Kerja - Zulkifli Zulkifli; Ahmad Syuhada; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2016)
Indonesia is a tropical country with a relatively high air temperatures. Increasing the temperature of the air outside the building space will increase in temperature in the room due to the heat transfer. Increasing air temperatures will occur in the thermal discomfort in space, resulting in a decrease in the effectiveness of work in the room. Conditions the average room temperature in May-September, 2013 in Banda Aceh is 330C-350C between the hours 11:00-13:00 WIB. This temperature is outside the limits of thermal comfort standards. To improve work efficiency in a room, the air must be conditioned to meet the thermal comfort standard SNI mounting method as a simple means of heat exchangers. Especially in the room that do not use often like indoor halls, and other sports, for this case by using the air conditioning air conditioner is too large investment and operational costs. In this study assessed a replacement air conditioning system with cold air in the conditioned room. In this study there are 3 air conditioning systems made is the replacement of AC system with fresh air into the space conditions, with the replacement of the air conditioning system is cooled with water to the space conditioning and replacement of the air conditioning system with a cooled with ice to the room conditioning. A room temperature of approximately 400C-500C air conditioned with new replacement 150C temperature-200C so that within 2-3 hours the room temperature dropped to 200C-250C and RH around 55-60%. So that the level of thermal comfort including thermal comfort within.